In the eye of the beholder: Meaning and structure of informal status in women's and men's prisons. Issue 1 (11th October 2020) - Kreager, Derek A.; Young, Jacob T.N.; Haynie, Dana L.; Schaefer, David R.; Bouchard, Martin; Davidson, Kimberly M.
Abstract: Applying an abductive mixed‐methods approach, we investigate the informal status systems in three women's prison units (across two prisons) and one men's prison unit. Qualitative analyses suggest "old head" narratives—where age, time in prison, sociability, and prison wisdom confer unit status—are prevalent across all four contexts. Perceptions of maternal "caregivers" and manipulative "bullies, " however, are found only in the three women's units. The qualitative findings inform formal network analyses by differentiating "positive, " "neutral, " and "negative" status nominations, with "negative" ties primarily absent from the men's unit. Within the women's units, network analyses find that high‐status women are likely to receive both positive and negative peer nominations, such that evaluations depend on who is doing the evaluating. Comparing the women's and men's networks, the correlates of positive and neutral ties are generally the same and center on covariates of age, getting along with others, race, and religion. Overall, the study points to important similarities and differences in status across the gendered prison contexts, while demonstrating how a sequential mixed‐methods design can illuminate both the meaning and the structure of prison informal organization.